Polymer porous membrane for flow battery as well as preparation method and application of polymer porous membrane
Through the preparation method of polymer porous membrane, the membrane structure is regulated by polymer and soft template, the low permeability and high cost of perfluorosulfonic acid film in the flow battery is solved, and efficient ion conduction and selectivity are achieved, improving the Battery performance and simplify production.
Patent Information
- Application Number
- CN202411422613.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
The perfluorosulfonic acid film has low ion selection permeability and high cost, and the chemical stability and ion selectivity of the non-fluoro ion exchange membrane are insufficient, resulting in poor battery energy efficiency of the flow battery.
Using the preparation method of polymer porous membrane, the membrane structure is regulated to improve ion conductivity and selectivity by selecting suitable polymers and soft template additives, including dissolving the polymer in an organic solvent to prepare a resin solution, adding soft templates and eliminating them. The bubbles form a porous membrane, controlling the distribution of the polymer and soft template to form a dense and porous layer.
It achieves high ion conductivity and selectivity, reduces battery resistance, improves the battery's Coulomb efficiency and energy efficiency, avoids the high cost of perfluoro resin, and simplifies the production process.
Smart Images

Figure CN119281145A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ion exchange membranes for liquid flow batteries, and in particular relates to a polymer porous membrane for liquid flow batteries and a preparation method and application thereof. Background Art
[0002] Wind and solar power generation is characterized by intermittency, randomness, volatility and unpredictability, which makes it difficult for the power system to maintain power balance. The energy storage system has the function of smoothing the fluctuations in renewable energy power generation. Aqueous liquid flow batteries are regarded as the ideal choice for the next generation of long-term energy storage technology due to their energy and power decoupling characteristics and extremely high safety.
[0003] Ion exchange membranes can selectively conduct ions and are one of the key materials for flow batteries. Perfluorosulfonic acid membranes are the mainstream products on the market. They are composed of a hydrophobic polytetrafluoroethylene skeleton and hydrophilic side chains containing sulfonic acid groups. They have excellent ion conductivity and high chemical stability. The synthesis of perfluorosulfonic acid resins involves fluorine chemicals, which is limited by harsh preparation conditions, resulting in high production costs. At the same time, the ion selective permeability of perfluorosulfonic acid membranes is low, which seriously restricts their commercial applications.
[0004] On the one hand, existing non-fluorine ion exchange membranes have insufficient chemical stability and poor ion selectivity, such as sulfonated non-fluorine ion exchange membranes, which lead to short life and serious electrolyte interpenetration problems; on the other hand, the ion (proton) conductivity is poor, such as polybenzimidazole membranes, which lead to high membrane resistance and poor battery energy efficiency. It is necessary to improve ion conductivity while ensuring ion selectivity and chemical stability. Therefore, the development of low-cost non-fluorine ion exchange membranes to improve ion selectivity while ensuring conductivity is an urgent problem to be solved in the field of flow batteries. Summary of the invention
[0005] The technical problem to be solved by the present invention is that the ion selective permeability of the perfluorosulfonic acid membrane is low and the cost is high. The shortcomings and defects mentioned in the above background technology are overcome, and a polymer porous membrane for liquid flow battery and a preparation method and application thereof are provided.
[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a polymer porous membrane for a flow battery comprises the following steps: (1) dissolving a polymer in an organic solvent to prepare a resin solution, wherein the polymer comprises one or more of polybenzimidazole, sulfonated polybenzimidazole, sulfonated polyetheretherketone, sulfonated polysulfone, sulfonated polyphenylsulfone or sulfonated polystyrene; (2) adding a soft template additive to the resin solution and stirring evenly to obtain a film-forming solution, wherein the soft template additive accounts for 1% to 40% by mass of the film-forming solution; the soft template additive includes one or more of glucose, fructose, galactose, lactose, ethylene glycol, polyethylene glycol, polyethylene glycol dimethyl ether or polyvinyl pyrrolidone; (3) The membrane-forming liquid is defoamed, cast into a membrane, and heated to volatilize, thereby obtaining a polymer porous membrane for a liquid flow battery.
[0007] This patent prepares a non-fluorinated ion exchange membrane. Starting from the regulation of the long-range structure and aggregated structure of the polymer, the membrane structure is regulated by adjusting the type and amount of soft template added, thereby achieving an improvement in ion conductivity and ion selectivity without negatively affecting the chemical stability of the membrane material.
[0008] The polymer selected in the present application is low-cost on the one hand, and has a certain chemical stability on the other hand, will not dissolve in aqueous electrolytes, has a certain ion exchange capacity, and can be selected according to the liquid flow battery system.
[0009] This application selects a suitable soft template additive and controls the amount of addition. Too much soft template additive will cause the additive to become a continuous phase during the film formation process, resulting in excessive porosity, no ion selectivity, and may not be dissolved in the solution; too little will cause it to be unable to be completely dispersed between polymer molecules and unable to form a continuous porous structure. The selected soft template is a common compound, which is cheap and has no obvious side effects when added in small amounts (<1%wt) to the all-vanadium electrolyte. It does not need to be removed after film formation, which can simplify the preparation process.
[0010] The soft template additives selected in the present application have a synergistic effect with the polymer. The soft template additives are all polyhydroxy compounds. The hydroxyl groups can generate intermolecular forces with the imidazole groups and sulfonic acid groups in the polymer selected in the present application, thereby changing the long-range structure and aggregated structure of the membrane.
[0011] Preferably, the mass concentration of the polymer in the resin solution in step (1) is 3-20%, and the dynamic viscosity of the solution is 100-100000 mPa / s.
[0012] Controlling the mass concentration range of the polymer in the resin solution ensures that the polymer can form a homogeneous solution in the solvent and does not undergo microphase separation in the solution. Limiting the dynamic viscosity can control the film-forming effect during the casting process. If it is too low, it is easy to leak and cannot be brought into the casting machine by the base film. If it is too high, it is difficult to level, resulting in poor film consistency.
[0013] Preferably, the density of the soft template additive in step (2) is 0.80-1.80 g / cm 3 .
[0014] Preferably, the dynamic viscosity of the molding liquid in step (2) is 100-5000 mPa / s.
[0015] During the solvent evaporation and drying process, the additives and polymers will undergo microphase separation to form a porous structure. The density and dynamic viscosity will affect the distribution gradient of the additives / polymers, thereby affecting the pore structure of the membrane.
[0016] Preferably, the defoaming in step (3) is performed by standing under reduced pressure, the vacuum degree during standing under reduced pressure is 0-1.0 MPa, and the defoaming time is 1-72 h.
[0017] Preferably, the temperature of the heating volatilization in step (3) is 60-120° C., and the heating time is 10-3000 min.
[0018] Under the same technical concept, the present application also provides a polymer porous membrane for a liquid flow battery, and the polymer porous membrane for a liquid flow battery is prepared by the above-mentioned preparation method.
[0019] Preferably, the polymer porous membrane for liquid flow battery comprises a dense layer and a porous layer, the porosity of the porous layer is 30%-60%, the pore size of the porous layer is above 1 nm, the dense layer is on one side or both sides of the porous layer, the pore size of the dense layer is below 1 nm, the porosity is less than 10%, and the thickness accounts for less than 5% of the thickness of the polymer porous membrane for liquid flow battery; Preferably, the ionic conductivity of the polymer porous membrane for liquid flow battery is ≥30 mS cm -1 , VO 2+ Permeability <10 -6 cm 2 / min, tensile strength ≥20 Mpa, elongation at break ≥30%.
[0020] Under the same technical concept, the present application also provides an application of a polymer porous membrane for a liquid flow battery, and the polymer porous membrane for a liquid flow battery is applied in a liquid flow battery.
[0021] Preferably, when the polymer porous membrane for liquid flow battery is used in a liquid flow battery, the 2 Under this condition, the battery coulomb efficiency is 98%~99.8%, and the energy efficiency is 75%~85%.
[0022] More preferably, the polymer porous membrane for liquid flow battery is used in a fully porous liquid flow battery.
[0023] The polymer porous membrane for liquid flow battery of the present invention is developed for the needs of all-vanadium liquid flow battery, is relatively more suitable, and can also be used in other liquid flow battery systems. According to the needs of different liquid flow battery systems, the type of polymer resin and the amount of soft template additive can be adjusted to regulate the membrane structure, thereby optimizing ion conductivity, ion selectivity and mechanical properties.
[0024] Preferably, when the polymer porous membrane for liquid flow battery is used in a liquid flow battery, the 2 Under this condition, the battery coulomb efficiency is 98%~99.8%, and the energy efficiency is 75%~85%.
[0025] More preferably, when the polymer porous membrane for liquid flow battery is used in an all-vanadium liquid flow battery, the 2 At the current density, the battery coulombic efficiency is ≥99% and the energy efficiency is ≥80%.
[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention selects a non-fluorinated ion exchange membrane when using a polymer porous membrane for a liquid flow battery, thereby avoiding the problems of high cost and low permeability of perfluorinated resins. On this basis, the present invention introduces a soft template, which is mixed with the resin solution when preparing the membrane solution. The density difference and intermolecular force are utilized to effectively adjust the upper pore structure during the solvent volatilization process, thereby obtaining better mechanical properties and lower ion transport resistance. A dense layer with controllable thickness is formed at the bottom layer, which can effectively improve the ion selective permeability of the polymer membrane. (2) The electrolyte solvent of the flow battery is an aqueous solution. The electrochemical window of water molecules limits the voltage range of the flow battery. The soft template additive selected in the present invention can either remain stable and not participate in the redox reaction during the charge and discharge cycle, or the product generated by the reaction will not affect the battery performance. The soft template additive will not volatilize during the preparation of the porous membrane, but exists in a solid form and fills between the polymer molecular chains. By retaining the soft template additive, not only can the pore structure be prevented from collapsing during the storage process, but the production and preparation process can also be greatly simplified, eliminating the post-processing process, and facilitating industrialization. (3) The polymer porous membrane for liquid flow battery prepared by the present invention has excellent performance and high ion conductivity. When used in all-vanadium liquid flow battery, the ion conductivity is 200 mA / cm 2 The battery coulombic efficiency is ≥99% and the energy efficiency is greater than or equal to 83%. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 This is a scanning electron microscope image of the cross section of the polymer porous membrane prepared in Example 1 provided by the present invention.
[0029] Figure 2 This is a graph showing the charge and discharge performance of the polymer porous membrane prepared in Example 1 of the present invention at different current densities in an all-vanadium liquid battery.
[0030] At 200 mA / cm 2 Under this condition, the battery coulombic efficiency is greater than 99% and the energy efficiency is about 83%, proving that the porous membrane has good ion selectivity and ion conductivity.
[0031] Figure 3 This is a scanning electron microscope image of the cross section of the polymer porous membrane prepared in Example 2 provided by the present invention.
[0032] Figure 4 This is a graph showing the charge and discharge performance of the polymer porous membrane prepared in Example 2 provided by the present invention at different current densities in an all-vanadium liquid flow battery.
[0033] At 200 mA / cm 2 Under this condition, the battery coulombic efficiency is greater than 99% and the energy efficiency is about 80%, proving that the porous membrane has good ion selectivity and ion conductivity. DETAILED DESCRIPTION
[0034] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0035] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0036] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0037] Example 1 This embodiment provides a method for preparing a polymer porous membrane for a flow battery, which specifically comprises the following steps: (1) Add 20 g of poly[2,2'-(p-oxybiphenyl)-5,5'-benzimidazole] to 1000 mL of N,N-dimethylacetamide and stir until completely dissolved to obtain a resin solution; (2) Add 27 g of glucose to the resin solution and stir until it is completely dissolved to obtain a molding liquid; (3) The prepared molding liquid was poured into a reactor and allowed to stand for 24 h under reduced pressure to defoam. The vacuum degree of the reactor was 0.95 MPa. The defoamed molding liquid was spread on the surface of the PET film by casting, and heated and dried at 80°C for 30 min. The dried polybenzimidazole film was removed from the surface of the PET film to obtain a polybenzimidazole porous membrane.
[0038] Figure 1 This is a scanning electron microscope image of the cross section of the polybenzimidazole porous membrane prepared in Example 1 provided by the present invention, in which obvious pore structure and dense layer can be seen.
[0039] The polybenzimidazole porous membrane prepared in this example was tested for surface resistance, ionic conductivity and VO 2+ The performance test of permeability was conducted in accordance with the industry standard, NB / T 42080-2023, and the test results are shown in Table 1; Table 1 Ion conductivity and pentavalent vanadium ion permeability of polymer membranes prepared by different methods
[0040] The polybenzimidazole porous membrane prepared in this example is applied to the all-vanadium liquid battery. 2 (4cm×4cm) carbon felt was used as electrode, graphite bipolar plate, 1.7 M vanadium electrolyte, and corresponding ion exchange membrane to assemble vanadium flow battery for rate test. The charge cut-off voltage was 1.6 V, the discharge cut-off voltage was 1.0 V, and different currents (current density 100mA / cm 2 ~300 mA / cm 2 ), that is, 1.6A~4.8A battery performance, 5 cycles under each current condition.
[0041] Figure 2 This is a graph showing the charge and discharge performance of the polymer porous membrane prepared in Example 1 of the present invention at different current densities in an all-vanadium liquid battery.
[0042] At 200 mA / cm 2 Under this condition, the battery coulombic efficiency is greater than 99% and the energy efficiency is about 83%, proving that the porous membrane has good ion selectivity and ion conductivity.
[0043] Example 2 This embodiment provides a method for preparing a polymer porous membrane for a flow battery, which specifically comprises the following steps: (1) Add 20 g of sulfonated polysulfone into 1000 mL of N,N-dimethylacetamide and stir until completely dissolved to obtain a resin solution; (2) Add 20 g of polyethylene glycol to the resin solution and stir until it is completely dissolved to obtain a film-forming solution; (3) Pour the prepared molding liquid into a reactor and place it under a vacuum of 0.95 MPa for 24 h to defoam. Spread the molding liquid on the surface of the PET film by casting and dry it at 80°C for 30 min. Remove the sulfonated polysulfone film from the surface of the PET film to obtain a sulfonated polysulfone porous membrane.
[0044] Figure 3 This is a scanning electron microscope image of the cross section of the polybenzimidazole porous membrane prepared in Example 2 provided by the present invention, in which obvious pore structure and dense layer can be seen.
[0045] The polybenzimidazole porous membrane prepared in this example was tested for surface resistance, ionic conductivity and VO 2+ The performance test of permeability, the test results are shown in Table 1; The polybenzimidazole porous membrane prepared in this example was applied to an all-vanadium liquid battery, and its charge and discharge performance under different current densities was tested; Figure 4 This is a graph showing the charge and discharge performance of the polymer porous membrane prepared in Example 2 provided by the present invention at different current densities in an all-vanadium liquid flow battery.
[0046] At 200 mA / cm 2 Under this condition, the battery coulombic efficiency is greater than 99% and the energy efficiency is about 80%, proving that the porous membrane has good ion selectivity and ion conductivity.
[0047] Comparative Example 1 The other methods of this comparative example are the same as those of Example 1, with the only difference being that N,N-dimethylacetamide of the same mass fraction is used to replace glucose as a blank control group.
[0048] The polybenzimidazole porous membrane prepared in this comparative example was tested for surface resistance, ionic conductivity and VO 2+ The performance test of permeability is shown in Table 1.
[0049] Comparative Example 2 The other methods of this comparative example are the same as those of Example 1, with the only difference being that the obtained polybenzimidazole porous membrane is placed in 3 M sulfuric acid and soaked at room temperature for 72 h to remove glucose, and then washed with deionized water and dried to obtain a polybenzimidazole porous membrane with the soft template removed.
[0050] The polybenzimidazole porous membrane prepared in this comparative example was subjected to performance tests of surface resistance, ion conductivity and VO2+ permeability, and the test results are shown in Table 1; It can be seen from Comparative Example 1 that the polymer membrane without a soft template has extremely low ion conductivity and cannot be used in liquid flow batteries; it can be seen from Comparative Example 2 that after using sulfuric acid to remove the soft template, the pore structure may collapse during the drying process, the electrolyte cannot be fully infiltrated in some areas, and the ion conductivity is significantly reduced.
Claims
1. A method for preparing a polymer porous membrane for a flow battery, characterized in that: The following steps are involved: (1) dissolving a polymer in an organic solvent to prepare a resin solution, wherein the polymer comprises one or more of polybenzimidazole, sulfonated polybenzimidazole, sulfonated polyetheretherketone, sulfonated polysulfone, sulfonated polyphenylsulfone or sulfonated polystyrene; (2) adding a soft template additive to the resin solution and stirring evenly to obtain a film-forming solution, wherein the soft template additive accounts for 1% to 40% by mass of the film-forming solution; the soft template additive includes one or more of glucose, fructose, galactose, lactose, ethylene glycol, polyethylene glycol, polyethylene glycol dimethyl ether or polyvinyl pyrrolidone; (3) The membrane-forming liquid is defoamed, cast into a membrane, and heated to volatilize, thereby obtaining a polymer porous membrane for a liquid flow battery.
2. The preparation method according to claim 1, characterized in that The mass concentration of the polymer in the resin solution in step (1) is 3-20%, and the dynamic viscosity of the solution is 100-100000 mPa / s.
3. The preparation method according to claim 1, characterized in that: The density of the soft template additive in step (2) is 0.80-1.80 g / cm 3 .
4. The preparation method according to claim 1, characterized in that: The dynamic viscosity of the molding liquid in step (2) is 100-5000 mPa / s.
5. The preparation method according to claim 1, characterized in that: The defoaming in step (3) is performed by reduced pressure standing, the vacuum degree during reduced pressure standing is 0-1.0 MPa, and the defoaming time is 1-72 h.
6. The preparation method according to claim 1, characterized in that: The temperature of the heating volatilization in step (3) is 60-120° C., and the heating time is 10-3000 min.
7. A polymer porous membrane for a liquid flow battery according to any one of claims 1 to 6, characterized in that: The polymer porous membrane for liquid flow battery is prepared by the preparation method according to any one of claims 1 to 6.
8. The polymer porous membrane for liquid flow battery according to claim 7, characterized in that The polymer porous membrane for liquid flow battery comprises a dense layer and a porous layer, the porosity of the porous layer is 30%-60%, the pore size of the porous layer is above 1 nm, the dense layer is on one side or both sides of the porous layer, the pore size of the dense layer is below 1 nm, the porosity is less than 10%, and the thickness accounts for less than 5% of the thickness of the polymer porous membrane for liquid flow battery; The ion conductivity of the polymer porous membrane for liquid flow battery is ≥30mS cm -1 , VO 2+ Permeability <10 -6 cm 2 / min, tensile strength ≥20 Mpa, elongation at break ≥30%.
9. An application of a polymer porous membrane for a liquid flow battery as claimed in any one of claims 1 to 8, characterized in that: The polymer porous membrane for liquid flow battery is applied in liquid flow battery.
10. The use according to claim 9, characterized in that When the polymer porous membrane for liquid flow battery is used in a liquid flow battery, at 200 mA / cm 2 Under this condition, the battery coulomb efficiency is 98%~99.8%, and the energy efficiency is 75%~85%.